Role of Interspecific Aggression in Distribution of Leaf Warblers in the Himalayan Region - Singh, Pratap; Rawat, G. S. (Indian Forester, 2014)
Bird species are distributed along elevational gradients in mountain regions with narrow altitudinal ranges. Physical and biological environment, competitive exclusion and ecotones have been suggested as spacing mechanisms of species along elevational gradients. Interspecific aggression among closely related altitudinal replacements has been found to be one of the most important mechanisms in spacing of species in tropical mountains. In the present study interspecific aggression among closely related warbler species was tested using heterospecific song playbacks. Out of four species pairs tested interspecific aggression was detected in one pair, and it is possible that other factors related to physical and biological environment and ecotones may be more important in spacing Himalayan birds.